Job-Finding Anxiety Among Associate Degree Health Students: The Role of Demographic Factors - Aysel Arslan; İfakat Atak (Uluborlu Mesleki Bilimler Dergisi, 2026)
The primary objective of this study is to examine the levels of job-finding anxiety among associate degree students enrolled in healthcare programs and to determine whether these levels differ according to demographic variables. A survey was administered to 340 associate degree students in the field of health. Descriptive statistics and difference analyses were performed using SPSS software in the analysis of the data. The findings revealed that students experience high levels of job-finding anxiety. Significant differences in anxiety levels were observed based on gender, income level, and place of residence, whereas no meaningful differences were found in relation to grade level or age. Furthermore, all relationships among the sub-dimensions of job-finding anxiety were positive and statistically significant. The anxiety experienced by associate degree students in healthcare programs regarding their future employment prospects is influenced by both individual and socio-economic factors. The study highlights the need for career counseling and psychosocial support mechanisms for health students. It also draws attention to the importance of employment policies tailored to the needs of future healthcare professionals.